THE INFLUENCE OF NEWS BROADCAST VIDEO AND MOTIVATION ON WRITING ACHIEVEMENT - Agustin, Ariya (Lentera: Jurnal Ilmiah Kependidikan, 2018)
This study was conducted by usingexperimental method. The objectives of the study were (1) to find out whetherthere is a significant difference in writing achievement between the eleventh graders who taught by using news broadcast videos and that of those who are not, (2) to find out whether there is asignificant interaction effect of news broadcasts videos and motivation in writing achievement of the eleventh graders (3) to find out whether there is a significant difference in writing achievement between the eleventh graders who have high motivation and those who have low motivation. The population of this study the was eleventh graders ofSMA Negeri 2 Palembang in the academy year of 2014/2015 consisting of 450 from 11 classes. The sample of the study are taken by using purposive sampling method. The totalof the samplesis 60. The results of the study are analyzed by using T-test and Two Way Anova. The results show that 1there is a significant difference in writing achievement between the eleventh graders who taught by using news broadcast videos and those who are not and there is a significant difference in writing achievement between the eleventh graders students who have high motivation and those who have low motivation based on t-test analyzed. Based ontwo way Anova, there is not any significant interaction effect of news broadcasts videos and motivation in writing achievement. Based on the result ofquestionnaire, the students agree that news broadcast videos motivate them to learn English